2009
DOI: 10.1089/jwh.2008.1293
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of High-Risk Human Papillomavirus in Female Sex Workers in Spain: Differences by Geographical Origin

Abstract: HR-HPV prevalence is very high in FSW and varies by geographic origin. Women of younger age and lower education level and those engaged in sex work for <1 year showed the highest prevalence, making them a priority group for cervical cancer prevention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
5
19
0
2
Order By: Relevance
“…FSWs represent a group at the highest risk for HPV infection, and the increased risk has been attributed to a high number of sexual contacts, unsafe sex behaviour, smoking, and low socioeconomic status (10,13,19). In our country, the prevalence of HPV infection among FSWs in the region, where the prevalence in women in the general population is relatively low (2%), has been found to be 20% (unpublished data).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…FSWs represent a group at the highest risk for HPV infection, and the increased risk has been attributed to a high number of sexual contacts, unsafe sex behaviour, smoking, and low socioeconomic status (10,13,19). In our country, the prevalence of HPV infection among FSWs in the region, where the prevalence in women in the general population is relatively low (2%), has been found to be 20% (unpublished data).…”
Section: Discussionmentioning
confidence: 81%
“…HR-HPV types are high in FSWs than in women from the general population. Therefore, they comprise the priority group for active surveillance against HPV infection and cervical cancer (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…12,34,35 As in existing studies, 36 we began with a full model that included all variables with a P value of less than .1 in bivariate analysis. We then used a backward stepwise approach to construct the final multivariate model.…”
Section: Methodsmentioning
confidence: 99%
“…10 Younger age and number of years in sex work also have been associated with increased HPV infection among sex workers. 1012 A global review on HPV in sex workers across 25 countries found high rates of HPV infection, including high-risk types (particularly serotypes 16 and 18) that have been linked to cervical cancer. 13 Some evidence also shows a high frequency of abnormal Pap test results among this population.…”
Section: Introductionmentioning
confidence: 99%
“…En el análisis multivariado las diferencias por origen geográfico se mantuvieron. Además de las diferencias de origen geográfico, las mujeres de menor edad, con un nivel educativo más bajo y las que habían trabajado en el comercio sexual menos de 1 año tenían una prevalencia de VPH-AR superior 21 .…”
Section: Figuraunclassified